2021
DOI: 10.3389/fpls.2021.663309
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Membranes and Lipid-Protein Interactions in the Mg-Branch of Tetrapyrrole Biosynthesis

Abstract: Chlorophyll (Chl) is essential for photosynthesis and needs to be produced throughout the whole plant life, especially under changing light intensity and stress conditions which may result in the destruction and elimination of these pigments. All steps of the Mg-branch of tetrapyrrole biosynthesis leading to Chl formation are carried out by enzymes associated with plastid membranes. Still the significance of these protein-membrane and protein-lipid interactions in Chl synthesis and chloroplast differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 324 publications
(530 reference statements)
0
12
0
Order By: Relevance
“…12H). The PLBs constitute the lipid reservoirs for developing thylakoids (Bykowski et al, 2020) and have been shown to prevent lipid peroxidation and RNA damage under oxidative stress conditions (Almsherqi et al, 2009; Solymosi and Mysliwa-Kurdziel, 2021). The PLBs have been observed in association with both cyanobacterial thylakoids and eukaryotic chloroplasts.…”
Section: Resultsmentioning
confidence: 99%
“…12H). The PLBs constitute the lipid reservoirs for developing thylakoids (Bykowski et al, 2020) and have been shown to prevent lipid peroxidation and RNA damage under oxidative stress conditions (Almsherqi et al, 2009; Solymosi and Mysliwa-Kurdziel, 2021). The PLBs have been observed in association with both cyanobacterial thylakoids and eukaryotic chloroplasts.…”
Section: Resultsmentioning
confidence: 99%
“…Physiological state of the accumulated Pchlide can be revealed by the analysis of fluorescence emission spectra measured at 77 K ( Belyaeva and Litvin, 2007 ; Solymosi and Mysliwa-Kurdziel, 2021 ). Two fluorescence bands can be easily distinguished with emission maxima at about 633 and 654 nm, similar for WT and lut2 mutant ( Figures 3G,H ).…”
Section: Resultsmentioning
confidence: 99%
“…In etiolated seedlings, at the cellular level, proplastids develop into etioplasts instead of chloroplasts (typical for light-grown plants). A paracrystalline lipid structure, called prolamellar body (PLB), is characteristic for etioplasts ( Solymosi and Aronsson, 2013 ; Armarego-Marriott et al, 2020 ; Solymosi and Mysliwa-Kurdziel, 2021 ). The biosynthesis of some protein subunits of photosynthetic complexes is inhibited, and the biosynthesis of chlorophyll (Chl) pauses at the stage of protochlorophyllide (Pchlide) formation, and they both require light to continue ( Tanaka et al, 2011 ; Pipitone et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations